Allergic Diseases New Insights - Pereira, Celso (IntechOpen, 2015)
Allergic diseases are one of the most prevalent diseases in the present with an undeniable correlation with development conditions and with the surrounding environment. Thus, it becomes imperative that the gradual understanding of the pathophysiology and treatment strategies may be convenient for wide dissemination in the scientific community. The chapters included in the book Allergic diseases New Insights addressed a variety of important topics related to distinct aspects related to allergy. The contribution of outstanding expert authors from many countries provided update reviews on basic, clinical and treatment aspects and put in evidence further research regarding the knowledge of immune system responses and key points of allergic inflammatory reactions.